Correlation between grammatical competence and pragmatic competence among Iranian university EFL learners / Seyedeh Sepideh Mojabi - Mojabi, Seyedeh Sepideh (2014)
This study sought to determine the levels of pragmatic competence among Iranian EFL learners and to correlate these levels with their levels of grammatical competence. In order to do this, separate tests were devised. One set of tests was designed to measure pragmatic competence. A second set of tests was devised to test grammatical competence. The difference between their pragmatic competence and grammatical competence was examined for any significant correlation between them. In addition, the effect of learning methods on the pragmatic and grammatical competence was tested. The findings show that there is a weak or no correlation between EFL Iranian university students’ grammatical competence and their pragmatic competence. The findings also show that learning methods do have a significant effect on the Iranian students’ pragmatic and grammar competence. In addition, the study shows a predominance of traditional teaching and learning practices in Iran.